Antibacterial Activity of Propolis Produced by Trigona spp. Against Campylobacter spp. - FATONI, AMIN; ARTIKA, I MADE; HASAN, AHMAD ENDANG ZAINAL; KUSWANDI, KUSWANDI (HAYATI Journal of Biosciences, 2009)
Propolis is believed to have antimicrobial, anti-inflammatory and immunostimulating activities. The objective of this study was to investigate the antibacterial activity of ethanol extract propolis (EEP) of Trigona spp. from Bukittinggi West Sumatera against Campylobacter spp. Antibacterial activity of the EEP was measured by disc diffusion method. The compound groups of the propolis were also analyzed on the existence of alkaloids, flavonoids, saphonins, tannins, steroids, and terpenoids. This study revealed that the EEP of Trigona spp. shows an antibacterial activity on Campylobacter spp. The compound groups detected in the EEP were flavonoids and tannins, suggesting that the antibacterial activity of propolis of Trigona spp. may be due to these compounds. Key words: Trigona spp., antibacterial activity, Campylobacter spp